Evaluating the efficacy of curcumin plus serratiopeptidase formulation in inflammatory acne: a quasi-experimental study - Shakila Junaid; Kiran Naz Khan; Farina Zameer; Muhammad Mudassir; Sadaf Bukhari; Neeta Maheshwary; Muhammad Athar Khan (Drugs in Context)
Background: Acne vulgaris is one of the most common dermatological illnesses affecting people worldwide. In Pakistan, approximately 9.4% of the population and between 5% and 16% of young adults are affected by acne vulgaris. Conventional therapies (topical benzoyl peroxide, retinoids, antibiotics and oral isotretinoin) are effective but limited by antibiotic resistance and side effects. Curcumin (a natural anti-inflammatory/antimicrobial from turmeric) and serratiopeptidase (a proteolytic enzyme with anti-inflammatory, anti-oedematous and antibiofilm properties) each show promise in acne treatment. This article evaluates the efficacy of a combined oral curcumin plus serratiopeptidase formulation as an adjunct to inflammatory acne therapy.